Articulating a diasporic identity: The case of Latin American filmmakers in Quebec - Marquez, Zaida (University of Ottawa (Canada), 2009)
The flow of immigrants to Canada continues to increase steadily. Questions regarding identity are thus unavoidable in order to understand how diasporic identities are constructed within a multicultural Canada. An important contribution to this debate is embedded in the cinematographic expressions that immigrants produce. Such cultural products serve not only as mean to represent themselves, but also to negotiate their positions in regards to Canadian society, as well as their countries of origin. The Latin American community is an interesting example, as multiple cultures, nations, histories, and identities are included within it. This study critically analyzes how identity is represented in the films produced by Latin Americans in Quebec. The analysis takes into account the films, the filmmaker's perspective and the conditions these documentaries were produced in. Given these elements, this research looks at how a Latin American identity is constructed from the diaspora, and what kind of cinematographic strategies the filmmakers use to articulate such an identity.
Keywords: Sociology, Ethnic and Racial Studies.; Cinema.